PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 015 GURUN PANJANG KOTA DUMAI - Jon Arpanis Jon Arpanis; Hendri Marhadi Hendri Marhadi; Gustimal witri Gustimal witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The Background of the this research is the teacher does not applay yet or use the learning model well in IPS learning process. The teacher is just explain the material without asking the student to find IPS concept, and do not make IPS as a real activity. Hence it is needed to do learning improvement by applying contextual teaching and learning (CTL) learning model. Contextual teaching and learning (CTL) learning model is one of the teaching approaches which is specifically designed to facilitate  the students learning proses which is accordance with procedural knowledge in well structured that can be taught in phase activity pettern, step by step. The application of this contextual teaching and learning (CTL) learning model is aimed to develop students learning which is accordance whith the pattern step by step. This research is in form of classroom action research. The aim of this research is to improve the students learning result at grade IV of elementary school 015 Gurun Panjang. After appliying the contextual teaching and learning (CTL) learning model, the data were obtained and would be processed by usis quantitative method. The formulation of the research is, “Does the application of contextual teaching and learning (CTL) learning model can improve IPS learning result of the students at grade IV in Elementary School Gurun Panjang?”. The quantitative data are in form of knowledge test and students understsnding throught cycle repetition test. On the base score, the students classical completeness were 50% at the firs cycle increasd become 59,37% at the second cycle increased again becom 81,25%. The average of students base score were 65,63 at the firs cycle had increasing again become 70,00 at the second cycle had increasing become 83,43. Keywords: Learning Model contextual teaching and learning (CTL), IPS Learning Result